2017
DOI: 10.14689/issn.2148-2624.1.5c3s4m
|View full text |Cite
|
Sign up to set email alerts
|

How Do High and Low Anxious FL Listeners Employ FL Listening Comprehension Strategies? Exploring Student Perspectives

Abstract: Abstract. There has been a growing body of research on the relationship between foreign language (FL) listening anxiety and FL listening comprehension strategy use; however, how these strategies are employed by learners with different listening anxiety levels is an area open to investigation. Based on such need, this study aimed at exploring FL listening comprehension strategies used by high and low anxious FL listeners in a Turkish EFL context. For this purpose, 15 high anxious and 13 low anxious listeners at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For instance, Gönen (2009) identified a negative relationship between these two constructs and revealed that when there was an increase in the anxiety levels of the learners, a decrease was found in the use of metacognitive strategies. The same negative correlation was expressed in Golchi (2012) and Berber and Kuru Gönen (2017)'s studies that low anxious learners utilized more metacognitive strategies, and also in Golzadeh and Moiinvaziri (2017) who voiced that though weak, there was a negative correlation between listening anxiety and metacognitive strategy use of the learners. Contrary to those, the current study reported a low positive relationship between FLLA and MLS use of learners.…”
Section: Conclusion Discussion and Implicationsmentioning
confidence: 60%
See 3 more Smart Citations
“…For instance, Gönen (2009) identified a negative relationship between these two constructs and revealed that when there was an increase in the anxiety levels of the learners, a decrease was found in the use of metacognitive strategies. The same negative correlation was expressed in Golchi (2012) and Berber and Kuru Gönen (2017)'s studies that low anxious learners utilized more metacognitive strategies, and also in Golzadeh and Moiinvaziri (2017) who voiced that though weak, there was a negative correlation between listening anxiety and metacognitive strategy use of the learners. Contrary to those, the current study reported a low positive relationship between FLLA and MLS use of learners.…”
Section: Conclusion Discussion and Implicationsmentioning
confidence: 60%
“…The link between listening anxiety levels of the learners and their metacognitive strategy uses was also the starting point of few studies in the literature (Berber & Kuru Gönen, 2017;Dalman, 2016;Golchi, 2012). For instance, Golchi (2012) investigated whether there is a link between anxiety, listening proficiency and listening strategy of the learners.…”
Section: Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 15 studies adopted situation-specific-based scales to measure FL listening anxiety, with 10 studies (15.2%) measuring general listening anxiety and five studies (7.6%) measuring listening test anxiety. Other studies that employed various approaches to measure FL listening anxiety were only minimally present; for example, seven studies measured FL listening anxiety under the approach of the sources of anxiety; eight studies measured FL listening under the approaches of learner characteristics and FL listening ability, Kim, 2000Kim, , 2011Kimura, 2008;Bekleyen, 2009;Wang, 2010Wang, , 2016Kiliç and Uçkun, 2012;Mohammadi Golchi, 2012;Capan and Karaca, 2013;Pae, 2013;Serraj and Noordin, 2013;Tsai, 2013;Afshar and Hamzavi, 2014;Choi and Chon, 2014;Movahed, 2014;Yamauchi, 2014b;Li, 2015;Rahimi and Soleymani, 2015;Zhai, 2015;Bang and Hiver, 2016;Berber and Gönen, 2017;Cheng, 2017;Halat and Özbay, 2018;Jee, 2018;Namaziandost et al, 2018;Babakhouya and Elkhadiri, 2019;Kutuk et al, 2019;Ranto Rozak et al, 2019;Fathi et al, 2020;Hutapea et al, 2020;Hamid and Idrus, 2021;Niimoto, 2021 Emotionality 33 50.0 Tension over English, emotionality, affective, listening anxiety Kim, 2000Kim, , 2011Kimura, 2008;Bekleyen, 2009;…”
Section: Measuring Foreign Language Listening Anxietymentioning
confidence: 99%